PICOLEARN: WEB-BASED LEARNING MEDIA DEVELOPMENT ON PRIMM APPROACH TO ENHANCE COGNITIVE PROCESS IN PROGRAMMING - Gustin, S. Sarah Nuraisya; Junaeti, Enjun; Arianti, Andini Setya (Universitas Indraprasta PGRI, 2025)
The Merdeka Curriculum emphasizes the attainment of Higher-Order Cognitive Processes. However, achieving these cognitive goals remains a significant challenge, particularly in programming education. This study focuses on the development and evaluation of PICOLEARN, a web-based learning platform utilizing the PRIMM (Predict, Run, Investigate, Modify, Make) approach to enhance students' cognitive processes in looping structure control programming. The research was conducted in Bandung, Indonesia, involving 35 vocational high school (SMK) students as participants. The object of the study was the learning of looping structures, a fundamental topic in programming. The learning media was developed following the ADDIE model, beginning with a needs analysis and culminating in the design of instructional materials, questions, and learner activities. The media was validated by experts, achieving an 81% feasibility score, classifying it as